Brawls Bring Buzz: Male Size Influences Competition and Courtship in Diadasia rinconis (Hymenoptera: Apidae). Issue 4 (29th August 2018) - Russell, Avery L; Buchmann, Stephen L; Sabino, William de O; Papaj, Daniel R
Abstract: Sexual selection on male body size in species with a female-biased sexual size dimorphism is common yet often poorly understood. In particular, in the majority of bee species, the relative contribution of intrasexual competition and female choice to patterns of male body size is unknown. In this field study, we examined two possible components of male mating success with respect to body size in the solitary bee Diadasia rinconis Cockerell (Hymenoptera: Apidae): 1) ability to procure a mate and 2) the duration of copulation. We found that larger males were better able to procure mates and copulated for shorter periods of time. Although consistent with sperm competition theory, differences in copulation duration were slight; possibly, the shorter copulations of larger males instead reflect in copulo female choice. Consistent with this notion, males engaged in complex courtship while mounted, characterized for the first time in any bee in such detail via audio recordings and high-speed, high-definition video. The number of pulses in male courtship behavior was also positively associated with copulation duration and may have stimulated females to continue copulating, thereby potentially allowing smaller males to transfer a full ejaculate. Females were shown to be potentially polyandrous and although we did not observe precopulatory rejection in the field, captive females frequently rejected copulation attempts by captive males. Our work indicates that intrasexual competition selects for increased body size in a solitary bee.